Literasi Matematis Siswa SMP Berdasarkan Adversity Quotient Dalam Memecahkan Masalah SPLDV - Pardosi, Romario Petrus; Budiarto, Mega Teguh; Rahaju, Endah Budi (Universitas Dr. Soetomo, 2022)
Abstract Mathematics understanding of students is not only about understanding the material but how students can use the knowledge they already have to apply in everyday life. The ability of students to take advantage of the role of mathematics in problems that occur in real life is called mathematical literacy. One of the materials that include solving mathematical problems and the mathematical literacy process of students at the junior high school level is the Two-Variable Linear Equation System (SPLDV). In solving SPLDV problems, students need problem-solving, reasoning, and communication skills. Many aspects can influence students in solving problems, including the ability of students' intelligence in facing a difficulty called Adversity Quotient. The purpose of this study is to describe the mathematical literacy of students in the quitter, camper, and climber categories in solving the problem of a two-variable system of linear equations. This research is qualitative descriptive research with a case study approach. Data collection techniques were carried out by giving SPLDV problem-solving tests and task-based interviews. From the results of solving the questions, 29 junior high school students in Paciran, the researchers chose 1 student from each category of a quitter, camper, and climber who had more complete and systematic answers than the other students. The results showed that there were differences in problem-solving of the three subjects in the components of formulating, interpreting, and applying. Keywords: mathematical literacy, two variable linear equation system, adversity quotient Abstrak Pemahaman matematika peserta didik tidak hanya tentang pemahaman materi saja tetapi bagaimana peserta didik mampu menggunakan pengetahuan yang sudah mereka miliki untuk diterapkan dalam kehidupan sehari- hari. Adapun kemampuan peserta didik dalam memanfaatkan peran matematika pada permasalahan yang terjadi di kehidupan nyata disebut disebut literasi matematis. Salah satu materi yang mencakup pemecahan masalah matematika dan proses literasi matematis peserta didik di tingkat SMP yaitu Sistem Persamaan Linier Dua Variabel (SPLDV). Dalam menyelesaikan masalah SPLDV peserta didik membutuhkan kemampuan pemecahan masalah, penalaran, dan komunikasi. Banyak aspek yang dapat mempengaruhi peserta didik dalam menyelesaikan masalah, antara lain kemampuan kecerdasan peserta didik dalam menghadap suatu kesulitan yang disebut Adversity Quotient. Tujuan penelitian ini yaitu mendeskripsikan literasi matematis siswa kategori quitter, camper, dan climber dalam memecahkan masalah sistem persamaan linier dua variabel. Penelitian ini adalah penelitian deskriptif kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan pemberian tes pemecahan masalah SPLDV serta wawancara berbasis tugas. Dari hasil penyelesaian soal, 29 peserta didik SMP di Paciran, peneliti memilih 1 peserta didik dari masing-masing kategori quitter, camper dan climber yang memiliki jawaban yang lebih lengkap dan sistematis dibanding dengan peserta didik lainnya. Hasil penelitian menunjukkan bahwa terdapat perbedaan dalam memecahkan masalah dari ketiga subjek dalam komponen merumuskan, menafsirkan dan menerapkan. Kata Kunci: Literasi Matematika, Sistem Persamaan Linier Dua Variabel, adversity Quotient